Off-Label Yellow Fever and Hepatitis A Vaccination in Traveling Children - Cecilia Muruzábal; Lorea Vicente; Lucía Escolano Taravillo; Blanca Bravo Queipo de Llano; Cristina Calvo; Milagros García López Hortelano (MDPI AG, 2024)
There are few data on yellow fever (YF) and hepatitis A (HA) off-label vaccination. Given the rising trend of travel to endemic countries, there is a growing necessity to broaden vaccination coverage among the pediatric population. For this reason, we aim to assess the adverse effects associated with off-label vaccination, with the ultimate purpose of expanding the vaccine spectrum. We analyzed ambispectively ninety-four children under 12 months of age who received YF or HA off-label vaccines. The YF vaccine was administered to children aged 6-9 months and those allergic to eggs (with a prior negative prick test and no history of anaphylaxis), while the HA vaccine was given to children aged 6-12 months. Overall, 71 (75%) were vaccinated against YF, and 57 (60%) against HA; 34 against both. All of them fulfilled off-label vaccination criteria. No immediate adverse effects (AEs) were reported. Mild common AEs (diarrhea, fever, or malaise) were experienced by 10.8% of patients within 10 days after vaccination. The rate of AEs associated with off-label vaccination for HA and YF is low, suggesting that the vaccines could be considered safe.